Development and Validation of Social Anxiety Disorder Instrument in Students: Testing Content Validity, Empirical Validity, and Reliability - Amna Riskya; Henny Indreswari; Khairul Bariyyah (Prophetic : Professional, Empathy, Islamic Counseling Journal, 2026)
This study aims to develop and examine the psychometric quality of an instrument for measuring social anxiety disorder among high school students. The instrument was developed using the Research–Development–Research (RDR) model, which consists of three main stages. The construct was developed based on the diagnostic criteria outlined in the DSM-5-TR, encompassing three dimensions: Fear of Negative Evaluation, New Situation Anxiety, and Peer Anxiety. The initial instrument consisted of 31 items, comprising favorable and unfavorable items. Content validity was assessed by two psychometric experts and a Guidance and Counseling Center using Aiken’s V coefficient. The results showed coefficients ranging from 0.833 to 1.000, indicating that all items demonstrated adequate theoretical relevance. Empirical item validity was subsequently tested involving 145 high school students. The results indicated that 28 items met the validity criteria, with Corrected Item-Total Correlation coefficients ranging from 0.181 to 0.733, exceeding the critical value of 0.163. Three items (P5, P9, and P11) were excluded due to ambiguous behavioral descriptions and potential cognitive bias associated with negation in reverse-worded items. Reliability analysis of the 28 valid items yielded a Cronbach’s Alpha coefficient of 0.904, indicating very high internal consistency. However, the high reliability coefficient may also suggest potential item redundancy, providing an opportunity for further item refinement. Overall, the 28-item instrument demonstrates satisfactory validity and reliability and can be utilized by school counselors as an early detection instrument for identifying social anxiety among high school students.